Distribution of Inheritance in the Javanese Ethnic Community of Bilah Barat District Labuhan Batu Regency From the Perspective of Islamic Law - Syauqon Hilali Nur Ritonga (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
The dividing of inheritance on Javanese civil of sub-regency Blade Barat the Regency of Labuhan Batu on Islamic law study that the dividing of inheritance is dividing inheritance based on system sagendhong sapikul and sighar semangka and divided the inheritance based on five pillars of system, those are; a) Angayani, b) Angomahi, c) Angayomi, d) Angayemi and e) Angamatjani. And the Islamic law sees it that the dividing inheritance no fitting to Islam's verse on the Koran and hadith both based on maharis study or faráidh study. It means the certain of dividing inheritance on Javanese ethnic of sub-regency Bilah Barat based on justice system, meanwhile on the Koran shows the boy has gotten two more then woman's right. And the effect approaches to three fights are the murder, fomenter, and stamping on close.